2017
DOI: 10.1007/s11274-017-2241-6
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of inulin-containing waste in industrial fermentations to produce biofuels and bio-based chemicals

Abstract: Inulins are polysaccharides that belong to an important class of carbohydrates known as fructans and are used by many plants as a means of storing energy. Inulins contain 20 to several thousand fructose units joined by β-2,1 glycosidic bonds, typically with a terminal glucose unit. Plants with high concentrations of inulin include: agave, asparagus, coffee, chicory, dahlia, dandelion, garlic, globe artichoke, Jerusalem artichoke, jicama, onion, wild yam, and yacón. To utilize inulin as its carbon and energy so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 52 publications
0
17
0
Order By: Relevance
“…K. marxianus is also distinguished by thermotolerance (Lane et al, 2011 ), and the fastest reported growth rate of any eukaryote (Groeneveld et al, 2009 ). Recent years have seen increasing interest in new applications such as production of biomolecules (Hughes et al, 2017 ; Lin et al, 2017 ), biocatalysis (Oliveira et al, 2017 ; Wang et al, 2017 ) and heterologous protein production (Gombert et al, 2016 ; Lee et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…K. marxianus is also distinguished by thermotolerance (Lane et al, 2011 ), and the fastest reported growth rate of any eukaryote (Groeneveld et al, 2009 ). Recent years have seen increasing interest in new applications such as production of biomolecules (Hughes et al, 2017 ; Lin et al, 2017 ), biocatalysis (Oliveira et al, 2017 ; Wang et al, 2017 ) and heterologous protein production (Gombert et al, 2016 ; Lee et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Inulin is a polysaccharide commonly found in roots, tubers, and plant rhizomes from common foods, including asparagus, chicory, garlic, onion, and artichoke [ 43 ]. A 2014 meta-analysis [ 44 ] of randomized controlled clinical trials involving two hundred and fifty-two subjects (four adult studies and one pediatric study that was included in this review) found that inulin improved stool frequency, stool consistency, and transit time.…”
Section: Resultsmentioning
confidence: 99%
“…It was first isolated and characterized by the German scientist, Valenti Rose, in 1804 from the roots of flowering plant Inula helenum [85]. Inulin can be found in roots of chicory ( Cichorium endivia ), Jerusalem artichoke ( Helianthus tuberosus ), or blue agave ( Agave tequilana ), where it accumulates as a means of energy storage [86]. Inulin, together with oligofructose, is a fructan, a sub-class of carbohydrate characterized by fructosyl–fructose links between monomers.…”
Section: Alternative Saccharidesmentioning
confidence: 99%